Sistem Informasi dan Akuntabilitas Publik di Tingkat Desa (Studi tentang Penerapan Sida Samekta dalam Mewujudkan Akuntabilitas Publik di Desa Karangwuni Kecamatan Rongkop Kabupaten Gunungkidul) - Nilawati, Evi; Bawono, Septiono Eko; Harvitrananda, Primanadia (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2020)
This study aims to determine the effectiveness of the village information system (VIS) Sida Samekta in achieving public accountability in Karangwuni Village, Rongkop Sub-District, Gunungkidul Regency. This research employs a qualitative descriptive approach. Data were obtained through secondary data, observation, focused group discussion, and in-depth interviews. The finding indicates that VIS was entirely effective for achieving its purpose, presenting poverty data, supporting citizen journalism, strategic suitability in customer satisfaction, and having certain values, such as inclusiveness, public literation, ease of information access, and innovation. This research shows that the effectiveness of the information system has achieved public accountability in legal accountability, program accountability, and financial accountability. This research suggests, in order to improve VIS Sida Samekta, it needs village policy and budget support, data integration, expanded stakeholder cooperation, and local government role in implementing Sida Samekta Award.Â  Â  Â